A case report: Posterior acetabular deficiency treated with femoral head autograft and hybrid total hip arthroplasty (Indian Journal of Case Reports, 2024)
As a choice for treating acetabular deficiencies, total hip arthroplasty (THA) is beset with many drawbacks, particularly in relation to untreated fractures and post-surgery complications. Furthermore, it is hard to ensure long-term fixation of the acetabular shell. In our case, a 52-year-old male manual laborer presented with complaints of a painful limp of the left lower limb with gross restriction of movements in the left hip joint. Previously, the patient had undergone open reduction and posterior acetabular wall plate fixation 2 years back and implant exit had been done 1 year before due to complaints of pain. We treated the patient with hybrid THA. To rectify the acetabular defect, we used a femoral head autograft, securing it with screws, and supporting it with a plate posteriorly. After 1 year, there was good graft consolidation sans acetabular component displacement as evidenced by radiography. A Harris hip score of 79.7 indicated good functionality. Therefore, hybrid THA with reconstruction is a good option for treating post-traumatic arthritis with acetabular wall deficiencies. Although the procedure is difficult to carry out, it yields better results in terms of lessened pain, enhanced stability, and better functionality.